TANGGUNGJAWAB HAKIM PENGAWAS DALAM PENGURUSAN HARTA DEBITUR PASCA PAILIT - Utama, Cholida; Holijah, Holijah (Muamalah, 2017)
Bankruptcy can happen for more rapid development of economic and trade issues which arise various debts that arise in the community. So also with the monetary crisis in Indonesia has given the unfavorable impact on the national economy, causing great hardship to the business community in resolving debts to continue its operations. So the need for an alternative solution for all parties to ensure the settlement of accounts payable business through bankruptcy institutions, and of the seizure is the expectation that all creditors receive payment of the balance of the proceeds from the seized assets.